Penerapan Perhitungan Harga Pokok Produksi Berdasarkan Proses Costing pada Rumah Potong Ayam : Studi Kasus PT X di Sidoarjo - Ria Galuh Yuli Pratiwi; Diana Zuhroh; Wiratna Wiratna; Tjandra Wasesa; Heri Toni (Jurnal Mahasiswa Manajemen dan Akuntansi, 2024)
Indonesia experienced an economic increase in the third quarter of 2023 of 4.94 percent per year, although slightly lower than 5.17 percent per year in the previous quarter. This is supported by increasing household consumption, consumer confidence and stable public purchasing power (Bank Indonesia Central Bureau of Statistics (BPS) data: November 2023). The growing economic growth in Indonesia allows entrepreneurs to open up more business opportunities in the business sector. With the increasing business of new companies, business competition both at home and abroad is getting tighter, resulting in global business competition. All economic sectors strive to improve the quality of production and income, because the company's main goal in building a business is to obtain the largest possible profit that is in line with the survival of the business actor. Therefore, to achieve this goal requires calculating the right selling price. Because company management does not know how to calculate the correct and competitive selling products, this calculation will definitely be a challenge for them. Selling price is defined as the amount of money given by a company to buyers or purchasing a product (Supriyono 2013:211). If the selling price is high then buyers will not buy the goods or may reduce purchases. However, if the selling price is low, it will affect revenue results and hinder the achievement of company goals. The selling price is influenced by production costs. If the cost of production is calculated incorrectly, the selling price used will also be incorrect. Therefore, it is important for business people to make decisions about how product selling prices are determined efficiently.